Diseño de una estrategia didáctica para la comprensión de procesos biológicos a través del funcionamiento de canales iónicos y la bomba de Na+ / K+ en la sinapsis neuronal. (2019)
This research presents the design of a didactic strategy based on the significant critical learning of Marco Antonio Moreira, and on the SQA technique of Julio Pimienta, in order to improve the teaching work and bring new strategies to the classroom with interactive learning activities that promote the development of basic skills in students, as proposed by the Ministry of National Education. The proposal is aimed at understanding biological processes such as response to stimuli and cell communication and recognition from ion channels and the sodium potassium pump. Failures determined from the analysis of teaching practice and knowledge tests of the José Miguel de la Calle Educational Institution.